Pelatihan Tata Rias Wajah bagi Tenaga Administrasi Wanita di lingkungan Universitas PGRI Banyuwangi - Efendi, Yuli Kartika (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
A working woman must be trying to have a beautiful appearance in daily activity. Administration officers atUniversitas PGRI Banyuwangi are serve students. These officers appearance has important rule in administration servicing.The appearance connected to service quality that effect the working performance. This training activity is followed by 12women who work in administration department. Make up training is conducted due to give knowledge and basic skill toworking woman which can improve their daily performance. This activity is done with lecture, discussion, and practicemethods. The result of the training shows that the participants are very enthusiastic. The make up knowledge and skill can beused to working and social activity